Clinical assessment of early tooth demineralization using polarization sensitive optical coherence tomography - Louie, Tiffany; Lee, Chulsung; Hsu, Dennis; Hirasuna, Krista; Manesh, Saman; Staninec, Michal; Darling, Cynthia L.; Fried, Daniel (Lasers in surgery and medicine, 2010)
Introduction The aims of this study were to test the hypothesis that polarization sensitive‐optical coherence tomography (PS‐OCT) can be used to non‐destructively measure and quantify the severity of the early demineralization of enamel on buccal and occlusal surfaces and assess the inhibitory effect of fluoride varnish in vivo. Methods A split mouth design was used to assess the effects of fluoride varnish on inhibiting dissolution on 20 test subjects. Orthodontic bands with a buccal window were cemented on the premolars and small incisions were produced on occlusal surfaces to serve as sites for plaque retention for enhanced demineralization. Bands were removed after 30 days and PS‐OCT scans were acquired in vivo of occlusal and buccal areas. Teeth were extracted, sectioned, and analyzed using polarized light microscopy (PLM) and transverse microradiography (TMR) for comparison with the PS‐OCT images. Results High contrast PS‐OCT images were acquired of both occlusal and buccal surfaces in vivo. Both occlusal and buccal surfaces, showed a significant difference (P < 0.05) in the integrated reflectivity (ΔR) between the “sound” and “carious” enamel groups. Although the mineral loss (ΔZ) and ΔR measured using TMR and PS‐OCT were less for the fluoride varnish‐treated buccal surfaces the difference was not statistically significant (P > 0.05). Conclusions Our results indicate that PS‐OCT can non‐destructively measure early enamel demineralization on the buccal and occulsal surfaces in vivo. Lasers Surg. Med. 42:898–905, 2010. © 2010 Wiley‐Liss, Inc.